Multidimensional Mass Spectrometry of Synthetic Polymers and Advanced Materials. Issue 6 (18th January 2017) - Wesdemiotis, Chrys
Abstract: Multidimensional mass spectrometry interfaces a suitable ionization technique and mass analysis (MS) with fragmentation by tandem mass spectrometry (MS 2 ) and an orthogonal online separation method. Separation choices include liquid chromatography (LC) and ion‐mobility spectrometry (IMS), in which separation takes place pre‐ionization in the solution state or post‐ionization in the gas phase, respectively. The MS step provides elemental composition information, while MS 2 exploits differences in the bond stabilities of a polymer, yielding connectivity and sequence information. LC conditions can be tuned to separate by polarity, end‐group functionality, or hydrodynamic volume, whereas IMS adds selectivity by macromolecular shape and architecture. This Minireview discusses how selected combinations of the MS, MS 2, LC, and IMS dimensions can be applied, together with the appropriate ionization method, to determine the constituents, structures, end groups, sequences, and architectures of a wide variety of homo‐ and copolymeric materials, including multicomponent blends, supramolecular assemblies, novel hybrid materials, and large cross‐linked or nonionizable polymers. Abstract : More dimensions for MS : Multidimensional mass spectrometry combines mass analysis with tandem mass spectrometry fragmentation and an orthogonal separation method, such as liquid chromatography (LC) fractionation or ion‐mobility spectrometry (IMS), to achieve top‐down characterization of the composition, end groups, connectivity, and architecture of synthetic materials. CCS=collision cross‐section; CE=collision energy.